EFEKTIFITAS PENGEMBANGAN E-MODUL MATEMATIKA BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS - Sonya Heswari; Sonya Fiskha Dwi Patri (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
This research is a research and development which aims to produce an e-module of mathematics based on ethnomatematics to improve students’ logical thinking skillsand their effectiveness in learning on rectangular flat figure material. The development model used ADDIE model research method which consist of analyze, design, develop, implementation, and evaluation. The research was conducted at MTsN 1 Sungai Penuh with the trial subjects being individual trials, namely mathematics teachers, small group trials, and large group trials by class VIIIA students. The instrument used was the expert team validation sheet, namely media and material validation, teacher response questionnaires and student responses, student perception questionnaires, and students' logical thinking ability tests. The results of the student perception questionnaire analysis, an average percentage of 82.7% was obtained. shows a